Strategy of the Independent Learning Program-Independent Campus (MBKM) for the Health Study Program Curriculum: Scoping Review - Bainuan, Lina Darmayanti; Yohanes Zenriano Tarigan (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Introduction: Independent Learning Program-Independent Campus (MBKM) is a policy issued by the Minister of Education and Culture since 2020 so that graduates are ready to face global challenges. Based on the policy issued by the Ministry of Education and Culture, it is necessary to adjust the strategy for the curriculum of the Health study program that already has provisions in the application of the curriculum. Since the establishment of the MBKM program in universities, the fact is that the curriculum of the health study program has not been able to adjust policies related to the MBKM program as a whole.  Therefore, a review of the published primary research is carried out to be able to provide comprehensive scientific evidence related to the MBKM program strategy for the health study program curriculum. Objective: This study aims to investigate the MBKM program strategy for the health study program curriculum. Method: Scoping review with a comprehensive search strategy was carried out using the Pubmed, SCOPUS, CINAHL, EMBASE and ProQuest database libraries and using the Science Direct and Google Scholar search engines, with full-text article criteria, ranging from 2021-2023 with Randomized Controlled Trial (RCT) and Cross-sectional Studies research designs. Based on the search results, there are six articles that meet the analysis criteria. Results: based on six articles, several health study programs were found to implement the MBKM strategy, but several obstacles were also found in the implementation of the MBKM strategy. Conclusions and Suggestions: the six articles are then grouped according to the MBKM strategy approach, namely staying focused on achieving SKL / CPL, still paying attention to the fulfillment of learning rights for a maximum of three semesters, students get learning experiences with additional competencies obtained from each study program, the application of students getting learning experience in the real world in accordance with the profile and scope of their field of work and the curriculum that has been designed and implemented is flexible and adaptable to the development of science and technology (scienfic vision) and the demands of the field of work (market signal). Each of these strategies is then used as an illustration in the implementation of the MBKM program for the health study program curriculum.